Against Single Stories of ‘Left Behind’ and ‘Triple Win’: On Agricultural Care Chains and the Permanent Subsistence Crisis - Bolokan, Dina (Frontiers in Sociology, 2021)
The single story of Moldova as the “country without parents” is unsettling. While it is true that villages in Moldova, as in other post-Soviet regions and global peripheries, are affected by intensive outmigration and labor mobility, the image is incomplete. In this article, I propose a different telling of this story: one that looks at and challenges the structural power relations visible in people’s lives in rural Moldova. It is a telling that points to the overall subsistence crisis in Europe and the relationship between neo_colonial entanglements and agricultural care chains. As such, this article aims to bring together reflections on labor migration, well-being in rural areas and the global care economy while seeking to decolonize subsistence production through the abolition of the international division of (re)productive labor.